Pengaruh Permainan Bola Pantul Terhadap Peningkatan Kemampuan Passing Bawah Siswa Ekstrakurikuler Bola Voli SMA Negeri 1 Soe - Veramyta Maria Martha Flora Babang; Maria Andriani Barek Ladjar; Amram Felipus Selan; Nurikhwan Aziz Arifin (Universitas Pendidikan Ganesha, 2026)
Based on the observations of researchers at SMA Negeri 1 Soe, the sport of volleyball taught in physical education, sports and health subjects must be further developed in extracurricular activities so that students can better master the techniques of playing volleyball. One technique that must be mastered is the volleyball underpass technique. In this case, the author sees that students who take part in extracurricular activities are still less skilled in carrying out down passing techniques. The aim of the research is to find out the effect of the bounce ball game on whether it can improve the bottom passing skills/ability of extracurricular students at SMA Negeri 1 Soe. This research is pre-experimental research. The research design used in this research is one group pretest posttest design. Based on the description of the research results and discussion in the previous chapter which analyzed the data using the SPSS version 20 program, the results of the normality test showed a p value (sig) > 0.05, which means the data was said to be normal, the results of the homogeneity test showed using Levene statistics a p value (sig) 0.430 > 0.05, which means the data has a homogeneous variance and also based on the results of the t-test, it shows a sig (2-tailed) value of 0.000 < 0.05, meaning Ha is accepted, which means there is a significant influence on improving the bottom passing skills of extracurricular students at SMA Negeri 1 Soe using the application of the game. bouncing ball. It is hoped that the results obtained in this research will be able to provide contributions from various parties as useful input.